The ethics of technology in medicine - Leone, Salvino (Medicina e Morale, 1990)
The increasingly sophisticated technology of medicine today involves methods which require constant attention, as far as their ethical implications are concerned. These implications are examined in relationship to the technological equipment, the patient, the physician who uses the equipment, and society which to a certain degree conditions its use. Finally the complex question of the control of technology is analyzed, and some ethical outlines are drawn from the conclusions.